Optimizing Osteogenic Differentiation of Ovine Adipose-Derived Stem Cells by Osteogenic Induction Medium and FGFb, BMP2, or NELL1 In Vitro - Emil Østergaard Nielsen; Li Chen; Jonas Overgaard Hansen; Matilda Degn; Søren Overgaard; Ming Ding (Hindawi Limited, 2018)
Although adipose-derived stromal cells (ADSCs) have been a major focus as an alternative to autologous bone graft in orthopedic surgery, bone formation potential of ADSCs is not well known and cytokines as osteogenic inducers on ADSCs are being investigated. This study aimed at isolating ADSCs from ovine adipose tissue (AT) and optimizing osteogenic differentiation of ovine ADSCs (oADSC) by culture medium and growth factors. Four AT samples were harvested from two female ovine (Texel/Gotland breed), and oADSCs were isolated and analyzed by flow cytometry for surface markers CD29, CD44, CD31, and CD45. Osteogenic differentiation was made in vitro by seeding oADSCs in osteogenic induction medium (OIM) containing fibroblast growth factor basic (FGFb), bone morphogenetic protein 2 (BMP2), or NEL-like molecule 1 (NELL1) in 4 different dosages (1, 10, 50, and 100 ng/ml, respectively). Basic medium (DMEM) was used as control. Analysis was made after 14 days by Alizarin red staining (ARS) and quantification. This study successfully harvested AT from ovine and verified isolated cells for minimal criteria for adipose stromal cells which suggests a feasible method for isolation of oADSCs. OIM showed significantly higher ARS to basic medium, and FGFb 10 ng/ml revealed significantly higher ARS to OIM alone after 14 days.